PENGARUH STRUKTUR AKTIVA, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP STRUKTUR MODAL: Studi Kasus pada Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016 - Fauzan Adji Saputra, - (2019)
This study aims to determine the effect of asset structure, sales growth, firm size, and profitability. Population in this study are agriculture companies listed in Indonesia Stock Exchange (IDX) 2014-2016. The technique of determination of the sample using the method of purposive sampling and obtained 12 agriculture companies with a research period of three years to obtain 36 units of samples. Data analysis was done using Microsoft Excel 2013 and hypothesis testing in this research using Multiple Regression Linear with SPSS 21.0 for Windows and significance level of 5%. The result of the research shows that asset structure, sales growth, and firm size has no significant effect on capital structure and profitability has significant negative effect on capital structure This study aims to determine the effect of asset structure, sales growth, firm size, and profitability. Population in this study are agriculture companies listed in Indonesia Stock Exchange (IDX) 2014-2016. The technique of determination of the sample using the method of purposive sampling and obtained 12 agriculture companies with a research period of three years to obtain 36 units of samples. Data analysis was done using Microsoft Excel 2013 and hypothesis testing in this research using Multiple Regression Linear with SPSS 21.0 for Windows and significance level of 5%. The result of the research shows that asset structure, sales growth, and firm size has no significant effect on capital structure and profitability has significant negative effect on capital structure